Learning Integrative Mathematics On The Set Material In The Al-Qur’an Study - Wulandari, Suci; Hendrawati, Novita Erni; Adawia, Aida; Dinantika, Tutus; Rofiki, Imam; Abdussakir, Abdussakir (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
This study aims to examine the set in the Qur’an. The study of the site can help both teachers and students in learning. Integrative mathematics learning can improve the set of knowledge integrated with the Qur'an and religious knowledge. The method used in this research is descriptive method to literature study. The results showed that the set in the Qur'an in the QS. Al-Fatihah verse 7, QS. Al-Fatir verse 01, QS. An-Nur verse 45, QS. Thaha verse 06, QS. Al Waqiah verses 07-10, and QS. Al-An'am verse 128